EFEKTIVITAS KELAMBU BERINSEKTISIDA TERHADAP NYAMUK An.sundaicus (DIPTERA: CULICIDAE) DAN PENGGUNAANNYA DI DESA SUNGAI NYAMUK, KALIMANTAN UTARA - Sugiarto Sugiarto; Upik Kesumawati Hadi; Susi Soviana; Lukman Hakim (SPIRAKEL, 2018)
Long lasting insecticide nets (LLiNs) are used in vector control programs to malaria elimination. Maintenance of LLiNs is an important factor to ensure the effectiveness of the bed nets. This study aimed to analyze the effectiveness of LLiNs against An. sundaicus and analyze knowledge, attitudes, practises (KAP). The research was conducted in the Sungai Nyamuk Village, Sebatik Sub District, Nunukan District - North Kalimantan. The method used in this research is the WHO bioassay cone test and questionnaires of KAP for the use of LLiNs. The efficacy test consists of the treatment and control groups. Treatment group was LLiNs that have been used for 6 months, 12-23 months and over 24 months, while the control group was bed nets without insecticide. The results showed that LLiNs have been used for 6 months had the highest effectiveness with mortality 24 hours and 1 hour knockdown An. sundaicus amounted to 94,13%. While LLiNs have been used for 12-23 months showed ineffective with 24-hour mortality is 71,74%, LLiNs more than 24 months (mortality 24 hours is 37,33%). KAP results showed a 100% respondents to accept the distribution of LLiNs, but not willing to wash the nets. The effectiveness of LLiNs is correlated with washing nets. The use of LLiNs to prevent malaria transmission will be effective if supported by good maintenance.